1990
DOI: 10.1042/bj2700771
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mannose receptor activity by proteolysis

Abstract: Macrophages express a receptor on the cell surface that functions to clear glycoproteins from the extracellular milieu. The activity of this receptor is sensitive to treatment with trypsin. In inflammatory situations, macrophages are activated and exposed to increased levels of extracellular proteases. Under these conditions, mannose receptor activity on the macrophages is diminished. We therefore decided to study the effects of trypsin treatment on the structure and activity of cell-associated and purified re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The MR is a member of the C-type lectin family [3] and has been purified from a variety of sources [4][5][6]. The MR is a single polypeptide of 175 kDa molecular mass with eight carbohydrate recognition domains that cooperate to mediate binding of mannose-containing ligands [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The MR is a member of the C-type lectin family [3] and has been purified from a variety of sources [4][5][6]. The MR is a single polypeptide of 175 kDa molecular mass with eight carbohydrate recognition domains that cooperate to mediate binding of mannose-containing ligands [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the isolation procedures yielded several protein bands after the first affinity chromatography of the crude liver extract on the t-PA Sepharose column, a second similar purification step showed only two bands, the 175,000 band and a minor band at 140,000, possibly derived from the 175,000 band by proteolytic degradation. This 140,000 fragment could indeed be generated by trypsin digestion of the intact protein, as suggested by Shepherd et al (58). The other proteins, which were eluted from the t-PA column, could not rebind in a second purification procedure.…”
Section: Discussionmentioning
confidence: 90%
“…5 MR internalizes rapidly in the presence of reactive oxygen intermediates released in RB and MR also internalizes in the presence of other inflammatory mediators like trypsin and antigenic products. 11,14,34,35 In such an environment clearance of products from inflammatory milieu by host defense receptors is reduced. 14 This study showed a significantly lower MR specific uptake in patients' PMv than that in controls (P = 0.023).…”
Section: Discussionmentioning
confidence: 99%
“…11,12,[34][35][36][37] Unfortunately we were unable to perform these techniques. However, in order to back-up the initial results we obtained from fluorescence technique we opted for PCR analysis.…”
Section: Discussionmentioning
confidence: 99%